Genome-wide study of mRNA degradation and transcript elongation in Escherichia coli - Chen, Huiyi (2018)
An essential part of gene expression is the coordination of RNA synthesis and degradation, which occurs in the same cellular compartment in bacteria. Here, we report a genome‐wide RNA degradation study in Escherichia coli using RNA‐seq, and present evidence that the stereotypical exponential RNA decay curve obtained using initiation inhibitor, rifampicin, consists of two phases: residual RNA synthesis, a delay in the interruption of steady state that is dependent on distance relative to the mRNA's 5′ end, and the exponential decay. This gives a more accurate RNA lifetime and RNA polymerase elongation rate simultaneously genome‐wide. Transcripts typically have a single RNA decay constant along all positions, which is distinct between different operons, indicating that RNA stability is unlikely determined by local sequences. These measurements allowed us to establish a model for RNA processing involving co‐transcriptional degradation, providing quantitative description of the macromolecular coordination in gene expression in bacteria on a system‐wide level.